PENILAIAN PERUBAHAN IKLIM BERDASARKAN KECENDERUNGAN DAN PERUBAHAN SUHU TAHUNAN DI MANOKWARI, PAPUA BARAT - Femmy Marsitha Barung; Wendel Jan Pattipeilohy; Robi Muharsyah (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2021)
A simple climate change assessment is carried out on annual air temperatures including average, maximum and minimum temperatures in Rendani, Manokwari for the period of 1993-2019. Parametric linear regression and nonparametric Mann-Kendall trend test (MK), Modified Mann-Kendall (MMK), Sen's Slope Estimator (SSE)are used to analyze trends and index numbers for analyzing the temperature changes. Homogenity test is performed using double mass curve and assumption of normality in the distribution is also investigated to meet the requirements of the linear regression trend test. There as a significant upward trend in the mean and minimum temperature with a slope of 0.029ºC/year and 0.069ºC/year, respectively. Meanwhile, the maximum temperature test shows no trend with a slope of 0.009ºC/year. Analysis of temperature changes using index numbers shows an increase in annual average temperature of 2.8% or 0.7°C, maximum temperature of 1.2% or 0.4°C, and minimum temperature of 3.1% or 0.8°C. The increase in annual air temperature in Manokwari City can generally be caused by several factors such as El Nino phenomenon, urbanization, population growth, and deforestation.